IMPLEMENTATION OF MORAL VALUES OF EDUCATION IN 2013 CURRICULUM ON ISLAMIC RELIGIOUS EDUCATION AT MADRASAH ALIYAH PERSIAPAN NEGERI 4 (MAPN 4) MEDAN - Mesran Mesran; Hadar Putra Daulay; Saiful Akhyar Lubis (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
Abstract. This study aims to determine the extent of the implementation of learning moral values that are applied to Islamic religious education in Madrasah Aliyah Persiapan 4 Medan. This research is qualitative using the method of observation and interviews on objects. The objects that are seen include; School Principal, Teacher, and other school equipment. The material studied includes the Syllabus, Lesson Plan, and other documents that show the activities of instilling moral values in this School. The results of this research indicate that the implementation of moral values in Islamic religious education has been carried out well in MAPN 4 Medan. This can be proven by the compilation of a moral learning syllabus and the integration of moral education in the lesson plan that must be made by the teacher. Thus, the implementation of instilling moral values in Islamic religious education has been going well in this MAPN 4 Medan. Keywords: Impelementation of Moral Values, 2013 Curriculum, Islamic Religious       Education, Madrasah Aliyah Persiapan Negeri 4 Medan.